Teleneurology in stroke management: costs of service in different organizational models - Handschu, Rene; Scibor, Mateusz; Nueckel, Martin; Asshoff, Dirk; Willaczek, Barbara; Erbguth, Frank; Schwab, Stefan; Daumann, Frank (Journal of Neurology, 2014)
Telemedicine is in increasing use in clinical neuroscience such as acute stroke care, especially by applying remote audiovisual communication for patient evaluation. However, telephone consultation was also used linking stroke centres to smaller hospitals. We compared costs of telestroke services using audiovisual and telephone communication in different organizational models. Within a small network in Northern Bavaria video-based teleconsultation (VTC) and telephone advice (TA) was provided for evaluation of acute stroke patients on a weekly rotation. The costs of the admissions process with or without one of both methods of telemedicine were calculated and compared from the perspective of the spoke hospital. Different levels of service and network size were modelled and costs of transfers as well as loss of revenues were calculated. Yearly total labour costs were 415,000 EUR for an on-site service VTC-service compared to 61,000 EUR in an on-call service. Additional costs for one teleconsultation were 109.55 EUR in VTC and 49.82 EUR in TA (VTC/TA ratio 2.2). The ratio decreased to 0.8 when accounting for costs of transfer and loss of reimbursement for all patients transferred as transfer of patients to the stroke centre was more frequent after TA (9.1 vs. 14.9%full-time on-site ser). Costs of one QALY gained by using VTC instead of TA ranged from 115.00 EUR to 515.86 EUR depending on the different models. In the first view TA looks like the less expensive method as it is easy to access and works without additional costs. When accounting for all disadvantages TA becomes slightly more expensive. In telestroke care VTC should be recommended as the method of choice also from an economic perspective.
EVALuna2:22264